Higher expression of calcineurin predicts poor prognosis in unique subtype of ovarian cancer - Bing Xin (Journal of Ovarian Research, 2019)
Abstract Background The role of calcineurin/NFAT signaling in ovarian cancer has been unknown. NFAT was significantly overexpressed in ovarian cancer tissues and that overexpression of NFAT was significantly associated with metastasis and poor prognosis on clinical tissue level. To investigate whether NFAT upstream protein, calcineurin (CN), affects the prognosis in various histological subtype of ovarian cancer (OC). Methods The association between CN and clinical features was analyzed in 50 OC patients treated from 2007 to 2012. CN expression was examined using immunohistochemistry. We observed the association of CN expression with the prognosis in these patients. Results CN expression was significantly increased in later-stage tumor tissue of serous carcinoma compared with those with early-stage. The expression of CN positively correlated with the serum cancer antigen 125 (CA125) level in ovarian clear-cell carcinoma and the serum alpha-fetoprotein (AFP) level in papillary serous cystadenocarcinoma. Particularly, higher CN expression in tumor tissues significantly correlated with reduced overall survival among patients with serous carcinoma. In addition, the serum cancer antigen 72–4 (CA72–4) level, serum carcinoembryonic antigen (CEA) levels, pathological stage, lymph node metastasis, and chemotherapeutic resistance were identified as significant prognostic factors in ovarian clear-cell carcinoma, serous carcinoma, or papillary serous cystadenocarcinoma. Conclusions CN is upregulated in ovarian cancer tissues with later-stage and that the expression of CN, CA72–4, and CEA was remarkably associated with poor prognosis in unique subtype of ovarian cancer. CN levels may be investigated for use as a prognostic biomarker for risk assessment in unique subtype of OC patients.